Efficient quantum circuits for Toeplitz and Hankel matrices - Mahasinghe, A; Wang, J B (Journal of physics. A, Mathematical and theoretical, 2016)
Toeplitz and Hankel matrices have been a subject of intense interest in a wide range of science and engineering related applications. In this paper, we show that quantum circuits can efficiently implement sparse or Fourier-sparse Toeplitz and Hankel matrices. This provides an essential ingredient for solving many physical problems with Toeplitz or Hankel symmetry in the quantum setting with deterministic queries.